Keberhasilan Kumur Doksisiklin sebagai Terapi Awal pada Kasus Periodontitis Stadium III Grade C - Ernie Maduratna Setiawatie; Ferlina Diah Ayu Yosi Pramita Asano; Esi Yuniza Fitrina (YARSI Dental Journal, 2026)
Introduction: Periodontitis progressively destroys tooth-supporting tissues. Conventional oral therapies often cause systemic side effects and fail to reach therapeutic levels in periodontal pockets. Doxycycline, studied for its local antimicrobial and anti-inflammatory effects, was used here as a 0.1% gargle. Case report: A 58-year-old woman presented with upper left tooth mobility, chewing pain, discomfort, and bleeding on brushing. Treatment included education, scaling/root planing, splinting, and twice-daily 0.1% doxycycline gargle post-brushing. After 2 months, gingival consistency had firmed, color had normalized, tooth mobility had reduced, and pocket depths had decreased. Discussion: Doxycycline inhibits subgingival pathogens and binds to dentin for sustained bacteriostatic action. It also suppresses collagenases (MMPs) from neutrophils and bacteria. Conclusion: In this case, 0.1% doxycycline gargle reduced gingival inflammation and improved clinical parameters as initial therapy before surgery, suggesting potential as a low-cost adjunct.